2022
DOI: 10.3389/fphys.2022.954760
|View full text |Cite
|
Sign up to set email alerts
|

Perceived impact of the menstrual cycle and hormonal contraceptives on physical exercise and performance in 1,086 athletes from 57 sports

Abstract: Female athletes train and compete under the potential influence of hormonal fluctuations during the menstrual cycle or during use of various hormonal contraceptives. Dysmenorrhea and premenstrual symptoms are common in the general population, as well as side effects of hormonal contraceptives. More detailed knowledge concerning prevalence and perceived impact of these symptoms on training and performance in different sports is required. The aim of the study was to 1) characterize perceptions of training and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 37 publications
5
21
1
Order By: Relevance
“…The influence of the menstrual cycle could be a factor to consider in program design, along with a host of other factors: nutrition, fatigue, sleep quality, stress, injury, motivation, and program enjoyment. We acknowledge that menstrual symptoms can influence exercise performance in some women ( 40 ), and thus it would be helpful to document this for reviewing long-term progress and adjusting a program. When reviewing the evidence as a whole—and the methodological shortcomings therein—we propose it is highly premature to conclude that short-term fluctuations in ovarian hormones appreciably influence acute exercise performance or longer-term adaptations to resistance training.…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…The influence of the menstrual cycle could be a factor to consider in program design, along with a host of other factors: nutrition, fatigue, sleep quality, stress, injury, motivation, and program enjoyment. We acknowledge that menstrual symptoms can influence exercise performance in some women ( 40 ), and thus it would be helpful to document this for reviewing long-term progress and adjusting a program. When reviewing the evidence as a whole—and the methodological shortcomings therein—we propose it is highly premature to conclude that short-term fluctuations in ovarian hormones appreciably influence acute exercise performance or longer-term adaptations to resistance training.…”
Section: Practical Recommendationsmentioning
confidence: 99%
“…Previous research has shown that symptoms related to the MC affect the performance level and wellbeing of many female athletes in various ways (6,(13)(14)(15)(16). For example, MC disturbance is one of the most well-known signs of Relative Energy Deficiency in Sport (RED-S), which can impair athlete performance negatively (e.g., increased risk of injury, decreased level of strength and endurance, and reduced training response) (17).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have mainly focused on senior athletes [e.g., (15,18,19)] and athletes in individual sports [e.g., (6,11,20)]. Since the JST is a critical stage in the talent development process (2,3) and that the MC may affect the performance level and wellbeing (6,(13)(14)(15)(16), it is crucial to explore the experiences of MC communication among junior athletes and their coaches in team sports as well. Knowledge about junior athletes is important since we might expect that they would consider talking about MC more difficult compared to senior athletes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations